A Analisis Dampak Kurikulum Merdeka Pada Pembelajaran Pendidikan Pancasila Terhadap Hasil Belajar Peserta Didik di SMA Negeri 10 Mataram: A. Dampak Implementasi Kurikulum Merdeka pada Pembelajaran Pendidikan Pancasila Terhadap Hasil Belajar Peserta Didik di SMAN 10 Mataram, B. Tantangan dan Hambatan dalam Implementasi Kurikulum Merdeka pada Pembelajaran Pendidikan Pancasila di Sman 10 Mataram,C. Solusi Menghadapi Tantangan dan Hambatan Implementasi Kurikulum Merdeka pada Pembelajaran Pendidikan - Amelia; Bagdawansyah Alqadri; Nurlatifa Nurlatifa (Jurnal Pendidikan Sosial Keberagaman, 2026)
This research was conducted due to the curriculum change and the demands placed on schools as the implementing institutions. The study aims to describe the impact of the Merdeka Curriculum on Pancasila Education learning and student outcomes at SMA Negeri 10 Mataram. The research employed a descriptive qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the implementation of the Merdeka Curriculum has brought positive changes in the planning, implementation, and evaluation of learning. Planning was carried out systematically through training, mentoring, and the preparation of teaching modules that integrate Pancasila values. Implementation provided teachers with space to innovate using varied methods, while evaluation was not only oriented toward final results but also included diagnostic, formative, and summative assessments that measured students’ knowledge, attitudes, and skills. Nevertheless, the implementation faced internal challenges such as teachers’ adaptation to new methods and students’ readiness, as well as external challenges including frequently changing policies, limited facilities, and minimal access to learning resources. To overcome these obstacles, the school focused on improving teacher competence through continuous training, workshops, mentoring, and supervision, while also encouraging learning innovations such as project-based methods, interactive discussions, real-case simulations, personal approaches, and the provision of motivation and rewards. Through this combination of strategies, Pancasila Education learning is expected to become more contextual, relevant, enjoyable, and meaningful, enabling students to more easily internalize Pancasila values, although full effectiveness still requires ongoing support and consistent evaluation. Keywords: Merdeka Curriculum; Pancasila education; Learning outcomes.